Graphene-based porous silica sheets impregnated with polyethyleneimine for superior CO2 capture - Yang, Shubin; Zhan, Liang; Xu, Xiaoyue; Wang, Yanli; Ling, Licheng; Feng, Xinliang (Advanced Materials, 2013)
It is demonstrated that graphene-based porous silica sheets can serve as an efficient carrier support for PEI via a simple nanocasting technology. The resulting materials possess thin nature, high PEI loading content and high thermal-conductivity. Such features are favorable for the efficient diffusion and adsorption of CO2 as well as the rapid thermal transfer during the CO2 capture process. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: CO; graphene; nanosheets; polyethyleneimine; silica